Critique of "Planetary Normal Mode Computation: Parallel Algorithms, Performance, and Reproducibility" by SCC Team From ETH Zurich - Burger, Manuel; Kleine, Jan (IEEE transactions on parallel and distributed systems, 2021)
This report analyzes the reproducibility of the article "Computing Planetary Interior Normal Modes with A Highly Parallel Polynomial Filtering Eigensolver" by Jia Shi et al. (Shi, 2018). To reproduce the results we perform different weak and strong scaling studies using a series of Mars models. All experimental runs were performed during the SC19 Student Cluster Competition on a four node Intel Skylake cluster. We show that the findings of the original article can be reproduced in a different environment.